Health Disparities Research with American Indian Communities: The Importance of Trust and Transparency. Issue 3 (11th July 2020) - Skewes, Monica C.; Gonzalez, Vivian M.; Gameon, Julie A.; FireMoon, Paula; Salois, Emily; Rasmus, Stacy M.; Lewis, Jordan P.; Gardner, Scott A.; Ricker, Adriann; Reum, Martel
Abstract: American Indian and Alaska Native (AI/AN) communities experience notable health disparities associated with substance use, including disproportionate rates of accidents/injuries, diabetes, liver disease, suicide, and substance use disorders. Effective treatments for substance use are needed to improve health equity for AI/AN communities. However, an unfortunate history of unethical and stigmatizing research has engendered distrust and reluctance to participate in research among many Native communities. In recent years, researchers have made progress toward engaging in ethical health disparities research by using a community‐based participatory research (CBPR) framework to work in close partnership with community members throughout the research process. In this methodological process paper, we discuss the collaborative development of a quantitative survey aimed at understanding risk and protective factors for substance use among a sample of tribal members residing on a rural AI reservation with numerous systems‐level barriers to recovery and limited access to treatment. By using a CBPR approach and prioritizing trust and transparency with community partners and participants, we were able to successfully recruit our target sample and collect quality data from nearly 200 tribal members who self‐identified as having a substance use problem. Strategies for enhancing buy‐in and recruiting a community sample are discussed. Highlights: Indigenous communities experience numerous health disparities associated with substance use disorder. Previous unethical research with Native communities serves as a barrier to research participation. Community based participatory research is a framework for overcoming barriers to research. Trust and transparency are crucial for conducting respectful research with Indigenous participants. We discuss effective strategies for recruiting a community sample of American Indian participants.